SAT0664 Is there an early ultrasonographic pattern in salivary glands in both primary and secondary sjogren syndrome?. (15th June 2017) - Iorgoveanu, VC; Mazilu, D; Saulescu, I; Vlad, V; Bojinca, V; Groseanu, L; Opris, D; Balanescu, A; Constantinescu, C; Predeteanu, D; Ionescu, R
Abstract : Background: Sjogren Syndrome (SS) affects mainly exocrine glands. Ultrasonography (US) demonstrates specificity and sensibility in major salivary glands (SG) evaluation. Recent data confirm US might be used as primary evaluation technique for its ability to show structural alterations of parenchyma [1]. Objectives: To assess the gray scale (GS) parenchymal inhomogeneity of major SG in patients with established primary and secondary SS and correlate with clinical and biological data. Methods: Consecutive patients with SS were recruited and SG US was performed. Inhomogeneity of glandular parenchyma was quantified binary on each gland. ESSDAI and ESSPRI scores were calculated. Statistics was performed with SPSS. Results: Twenty one (42.85% primary SS, 90.47% female) consecutive patients were included. Mean age was 53.66+/-12.99 years and disease duration 5.33+/-3.74 years. Antibody SSA/SSB presence was found in 85.7% (18/21). ESSDAI mean was 8.67+/-8.9 (0–29), ESSPRI 10.13+/-5.59 (0–20). There were no differences regarding ESSDAI and ESSPRI in the two groups (primary and secondary SS). Right parotid gland showed alterations in 71.4% patients (77% with primary SS, 66% with secondary SS). Frequently inhomogeneity was found in all major SG (33%, 22% left and right submandibular, 77%, 44.4% left and right parotid glands) in primary SS. Both submandibular glands were symmetrically involved (p<0.02). Duration of disease was negatively correlated to inhomogeneity of right parotid gland (p<0.02). Conclusions: Inhomogeneity in major SG in GS US was found in the majority of patients with primary and secondary SS. The symmetrical involvement of submandibular glands was significant. The inhomogeneity appears in the early period of diagnosis. No major differences were found between two groups. References: Damjanov N, Milic V, Nieto-González JC, Janta I, Naredo E. Multiobserver Reliability of Ultrasound Assessment of Salivary Glands in Patients with Established Primary Sjögren Syndrome. J Rheumatol. 2016 Oct;43(10):1858–1863. Disclosure of Interest: None declared